The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/1043659608325841
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Migration on the Health of Voluntary Migrants in Western Societies

Abstract: The authors reviewed literature on the health of voluntary migrants to Western societies and factors affecting their health. Health indicators include mortality rates and life expectancy, birth outcomes, risk of illness, patterns of deteriorating health, cardiovascular disease, body mass index, hypertension, and depression. Multiple factors explain variability, including length of residence and acculturation, disease exposure, life style and living conditions, risky behaviors, healthy habits, social support ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 59 publications
(73 reference statements)
4
113
0
Order By: Relevance
“…The differences in height between migrants and sedentees may support the supposition that healthier individuals are more likely to migrate (Lassetter and Callister 2009). However, overall, the study populations in London and Sylhet were matched for levels of affluence: only those groups with the means to migrate to the UK were included in the study.…”
Section: Predictionmentioning
confidence: 96%
“…The differences in height between migrants and sedentees may support the supposition that healthier individuals are more likely to migrate (Lassetter and Callister 2009). However, overall, the study populations in London and Sylhet were matched for levels of affluence: only those groups with the means to migrate to the UK were included in the study.…”
Section: Predictionmentioning
confidence: 96%
“…The process which a minority group adopts the dietary practice of the host country is called dietary acculturation and can be multidimensional, dynamic and complex (Satia-Abouta et al, 2002). Dietary acculturation can be observed on migration to another country and might be detrimental for health when it associated with changes, such as, less healthy diet (Lassetter and Callister, 2009). Satia-About a et al (2002) found that highly educated immigrants and those with similar cultural or physical characteristics with the host country, are more likely to acculturate with considerable facility, which may mean adopting of some unhealthy practices.…”
Section: Introductionmentioning
confidence: 99%
“…Immigration entails a readjustment to a new life and has previously been shown to influence health in both psychological and physiological ways [5,6]. The health of immigrants could be affected by factors on both the individual level and the group level because of societal factors both in their home country and in the new country [7,8].…”
Section: Introductionmentioning
confidence: 99%